(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s
(3ChdgG (B:s
(3hjHJOF HCNHGQ GdYHGS Hf GdCMfa s
(3BNQgG (B:s
(3hjfJgi Edi PcQ ai OhfJ dg UfYI ef NdaGA Hfi GdYHGS s
(3GdfSNI GdKGefI YTQs
(3hQO CjVkG JMJ Qbe (B2176s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B78s
Keywords: (3GdCOHs